PENCEGAHAN MENINGKATNYA KASUS BUNUH DIRI MAHASISWA: SEBUAH ALARM BAGI KAMPUS DAN MASYARAKAT - Naylla Rachma Edhisty; Mirna Nur Alia Abdullah (SABANA: Jurnal Sosiologi, Antropologi, dan Budaya Nusantara, 2025)
This study aims to raise awareness and identify preventive measures in reducing suicides among university students, caused by academic pressure, mental disorders, and lack of social support. The research method used a literature review with an analysis of 13 relevant articles from journals accessed through Google Scholar, using the keywords "suicide among college students" and "suicide prevention." The results showed that campuses can play a significant role in preventing suicides by providing mental health services, increasing literacy related to suicide issues, and building support communities. The conclusion of this study emphasizes the importance of collaboration between campuses, communities, and individuals in creating an environment that supports students' mental health. This literature review highlights various factors that influence the occurrence of suicide among university students, including academic pressure, lack of social support, and mental disorders such as depression and anxiety. Data from various sources indicate an increase in suicide cases in Indonesia, particularly among young adults. This study emphasizes the need for comprehensive prevention efforts, including self-management programs, the use of technology for mental health literacy, and active participation from the community and campuses in creating a supportive environment